Exploring Aboriginal aged care residents' cultural and spiritual needs in South Australia - Nina Sivertsen; Ann Harrington; Mohammad Hamiduzzaman (BMC, 2019)
Abstract Background Attention to culture and its impact on health care can improve the quality of care given, add to our understanding of health care among culturally diverse populations, and encourage a more holistic approach to health care within general care. Connection to culture is important to Aboriginal peoples, and integrating Aboriginal culture into general care in residential aged care facilities may contribute to improving care delivery and outcomes for residents. The literature to date revealed a lack of understanding of the capacity of residential aged care and the health practices of carers in relation to providing cultural care for Aboriginal people. This study aimed to explore how cultural care needs are maintained for Aboriginal residents from their own and their carers' perspectives. Methods Applying an Aboriginal centered research method, an Interpretive Descriptive Approach was used as a theoretical framework to explore data in this study. Semi structured audio-recorded interviews were conducted. An additional file provides a complete description of the interview questions used as a guide for the study [see Additional file 1]. Three Residential Aged Care Centres, in South Australia were used i.e., two rural from centres and one urban metropolitan centre. Seven Aboriginal residents and 19 carers participated in interviews. Data was transcribed and an interpretive analysis was employed to code the transcribed data for themes and sub-themes. The study was guided by an Aboriginal community advisory group with an aim to work under the principle of reciprocity; giving back to the communities, participants and those where the research results may have been relevant. Results Three themes emerged from the views of the residents and carers: (i) lack of resources and funding; (ii) care practice; and (iii) marginalisation of Aboriginal culture within aged care facilities. Conclusion The findings suggest that carers and residents believe cultural inclusion in general care practices may enrich Aboriginal residents' daily life, health and well-being in residential aged care facilities. This study may provide carers, aged care centre managers and policy makers with information on the need of resources, funding, organised care plan and management, and cultural competency of carers to be considered to improve Aboriginal aged care protocols for integrating cultural care into practice.